The Effect of ESG Risk Rating and Ownership Concentration on Firm Value: Leverage and Size as Moderation - Harold Kevin Alfredo; Euis Mufahamah; Anita Anita; Lestari Wuryanti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of leverage and company size as moderating variables on the relationship between ESG Risk Rating and ownership concentration on firm value. This research is included in the type of quantitative research and uses companies listed on the Indonesia Stock Exchange and have an ESG Rating value by Morningstar Sustainalytics. This research method uses linear regression in calculating the effect of independent variables (ESG Risk Rating, and ownership concentration) moderated by Leverage, and Firm Size variables on the dependent variable (Tobin's Q). The results found that the impact of firm size and leverage on the moderation of ESG score with firm value and the moderation of ownership concentration with firm value is not uniform. Specifically, leverage exerts a more substantial effect as a moderator between ESG risk score and ownership concentration and firm value than firm size.